Two consecutive cases of thyroid storm following radioactive iodine therapy for Grave’s disease - M., Azura Dina; AW, Norasyikin; Sukor, Norlela; Mustafa, Norlaila; WS, Wan Juani; Shahar, Mohammad Arif; Omar, Ahmad Marzuki; R, Subashini; Loh, Huai Heng; O, Mohd Rahman; Kamaruddin, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2014)
Background: Radiation thyroiditis is a known complication of radioactive iodine therapy (RAI) resulting in mild exacerbation of thyrotoxic symptoms. However, thyroid storm following RAI is rare. Case Reports: Case 1: A 33-year-old lady with long standing Grave’s thyrotoxicosis was given 15mCi of radioiodine 1-131 and developed worsening palpitation, sweating, tremor, fever, vomiting and diarrhea two days after treatment. At presentation, she had tremor and severe diaphoresis with heart rate of 141bpm and temperature of 39.8oC. She had small diffuse goiter and her weight was 54kg with BMI of 21.4kg/m2. There was no arrhythmia or heart failure and other systems examination was unremarkable. Her thyroid function test showed TSH <0.01uIU/ml, FT4 65.43pmol/l and FT3 28.09pmol/l. Her Burch-Wartofsky score was 70. She was treated as thyroid storm and as her blood culture was positive for E.coli she was given intravenous Ceftriaxone 1g OD. She made full recovery following treatment with lugol’s iodine, prophylthiouracil, propranolol, hydrocortisone and adequate hydration. Case 2: A 16-year-old girl with persistent thyrotoxicosis since 2010 presented five days after given 15mCi of RAI as her family noted that she progressively became irritable, restless and insomniac. These were associated with vomiting and diarrhea. At presentation, GCS was 12/15 with heart rate 110bpm and temperature 37oC. There was no palpable goiter and her weight was 55kg with BMI of 21.5kg/m2.There was no meningism or focal neurological deficit and other system examination was unremarkable. Her thyroid function test showed TSH <0.01uIU/ml, FT4 >77.22pmol/l and FT3 >46.08pmol/l. Her Burch-Wartofsky score was 55. Full neurological recovery occurred after 72 hours of treatment with hydration, lugol’s iodine, methimazole, propranolol and dexamethasone. Discussion: For the first case, the thyroid storm could be precipitated by the E.Coli infection. Her previous medical record showed history of lowgrade squamous intraepithelial lesion of the cervix, which usually precedes cytoplasmic intraepithelial neoplasia of the cervix. No plausible cause was found for the second case. Other possible causes that may contribute to the occurrence of the storm in these cases was usage of high doses of iodine 131 in relatively low BMI patients with small or no goiter. As the patients were given radioiodine within two consecutive days, the quality and integrity of the radioiodine substance maybe a factor contributing to this phenomenon. Comment: Although rare, thyroid storm can be precipitated by RAI and it is mostly severe and can be fatal.